Avaliação da distribuição das chuvas em municípios da região oeste no Estado do Paraná - Bilski, Joyce Gracielle Chies (2011)
Agriculture is one of the main economic activities of western Paraná, thus being of great importance for that region to analyze its rainfall patterns for the knowledge of their distribution. The objective of this study was to identify the presence of rainfall spatial distribution patterns as well as to identify the months of occurrence of water deficiency, based on Thornthwaite e Mather water balance, for the following cities in western Paraná: Foz do Iguaçu, São Miguel do Iguaçu, Santa Helena, Cascavel and Salto Caxias.